CLINICAL FEATURES OF ACUTE RHEUMATIC FEVER IN CHILDREN AT THE PRESENT STAGE - Umarova S. S.; Nabiyeva F. S.; Diamatova D. N. (International Journal of Innovations in Engineering Research and Technology, 2023)
Despite significant progress in reducing the incidence, acute rheumatic fever (ARF) has been observed in all countries of the world over the past decades. Determining the features of the course of the disease is important for timely diagnosis, which requires a thorough analysis of clinical, laboratory and instrumental data.